Farmers Empowerment Model For Improving Beef Farming Business In North Sulawesi - Lainawa, jJolyanis; Endoh, Eusebius K.M. (Jurnal Ekonomi Pertanian dan Agribisnis, 2023)
The need for beef consumption in North Sulawesi is increasing disproportionately to the amount of production produced due to limited human resources for human resources of farmers. Empowerment of farmers is an alternative strategy, because it is a process to improve the business and welfare of farmers. The purpose of this research is to develop the concept of empowering beef cattle farmers in North Sulawesi as a strategic model towards the process of changing the rearing system from an extensive traditional orientation to an intensive commercial one. Data obtained from interviews with 50 respondents provided, with interview techniques, FGD, Library Studies and BPS support, then analyzed using a qualitative descriptive approach, strategy formulation and Spearman Rank correlation to determine the significance relationship. The results of the analysis state that North Sulawesi has the potential for resources of the number of farmers it has as well as available land and animal feed production resources. So it is possible to make changes to the maintenance system. There is a significant relationship between the Counseling, Literacy, Institutional, Partnership, Entrepreneurship, Competitiveness, Production Facilities variables on Farmer Empowerment, interpreted as "Very Strong" correlation coefficient with the value of each correlation; 0.899**, 0.890**, 0. 650**, 0.803**, 0. 750**, 0.658**, 0.891**, where this indicates a priority factor in empowerment of beef cattle farmers in North Sulawesi. Furthermore, the strategy model is; participation, leadership, independence, sustainability based on modern extension, information literacy, cooperative farming, utilization of local production factors, entrepreneurship and market driving force development.